Intra-Sentential Code Mixing in the YouTube Podcast by Prilly Latuconsina Featuring Agatha Chelsea - Ni Kadek Arik Sumarni (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study aims to analyze the phenomenon of code mixing in a YouTube podcast by Prilly Latuconsina featuring Agatha Chelsea entitled Prilly Latuconsina: Bisnis Kapal Laut Berawal Dari Suka Mancing?! – Safe Space. This study applied a qualitative descriptive method to describe the forms and reasons for code mixing. Data were obtained through listening, note taking, and transcription of conversations, then analyzed using Hoffman's theory. The results showed that the dominant form of code mixing was intra-sentential code-mixing in the form of words and phrases, such as privilege, chill, learning process, and wrap up. The reasons for code mixing included vocabulary needs, emphasis on meaning, language habits, and a communication style that were considered more modern. These findings confirmed that code mixing in podcasts not only functioned as a linguistic strategy but also represented social identity, the influence of globalization, and the trend of bilingualism among Indonesia's younger generation